Detection & Distinction of Colors using Color Sorting Robotic Arm in a Pick & Place Mechanism - Amin, Uzma; Ahmad, G.; Liaqat, N.; Ahmed, M.; Zahoor, S. (2014)
Color sorting Robot is one of the useful, costless and fastest systems in Industrial applications to reduce manual working time and provides less human mistake when manual system is undertaken. The objective of this project is to design an efficient, microcontroller based system that pick up right color of objects and put it down at right place to optimize the productivity, minimizing the cost of the products and decreasing human mistakes. The controller used is a PIC Microcontroller (18F452) having high speed performance, low cost and 32 K bytes program memory. It communicates with color sensor TCS 3200 and various motor modules in real time to detect the right color object and to control the arm movement. Designed system can pick objects of 1kG weight and arm can rotate up to 3600 . Also, the use of easily available components reduces the manufacturing and maintenance costs. The design is quite flexible as the software can be changed according to specific requirements of the user. This makes the proposed system to be an economical, portable and a low maintenance solution for industrial applications.